Bacterial Contamination of the Anesthesia Workplace and Efficiency of Routine Cleaning Procedures: A Prospective Cohort Study. (May 2016) - Goebel, Ulrich; Gebele, Nicole; Ebner, Winfried; Dettenkofer, Markus; Bürkle, Hartmut; Hauschke, Dieter; Schulz-Stübner, Sebastian
Abstract : In this prospective cohort study, 200 decontamination (cleaning and disinfection) procedures of the anesthesia workplace either by anesthesia nurses or by specially trained housekeeping staff were monitored. Time used by housekeeping staff was shorter (1.2 ± 0.1 vs 2.6 ± 0.2 minutes on average, data are mean ± SEM; P < 0.0001) with less visible marker spots (14.4 ± 0.68 [55%] vs 17.3 ± 0.75 [66.7%] on average, data are mean ± SEM; P = 0.0041), and the bacterial load showed a decrease (≅67%, P < 0.0001) compared with anesthesia nurses. Specially trained housekeeping staff outperformed anesthesia nurses in cleaning the anesthesia workplace. Specific training for anesthesia workplace cleaning is supported by these findings.